Another Lunatic Express or a Mega Project of Dynamic Ramifications: Kenya's New Standard Gauge Railway - Kathuri, Rachael Wakio (European Journal of Applied Sciences, 2025)
When the British were allocated the British East Africa protectorate, later Kenya Colony, in the Berlin Conference in 1888, they did not want to invest as much in the new dark territory. Subsequently, the Imperial British East Africa Company (IBEACo.) was formed to manage the territory. The Company was soon building the Mombasa Uganda railway line from Mombasa to Kampala dubbed the lunatic express by many who felt it was going to nowhere and had nothing to achieve. Many years later in 2012, when the Kenyan government in liaison with the Chinese government embarked on building the Standard Gauge Railway, many people echoed the very words and almost rechristened it the lunatic express. This paper examines the Standard Gauge Railway project in Kenya as an exemplification of the evaluation of multi-international projects particularly in developing countries and specifically in Kenya. Findings indicate that the SGR project does positively impact on the transport system although there are several underlying issues that require to be resolved in order for the project to derive maximum benefits. The study recommends enhanced stakeholder engagement, transparent management of project finances, and continuous evaluation to ensure visibility, sustainability and accountability in large infrastructural projects like the SGR.